„Lubmy swoje” or, winged words coming from songs - Rosińska-Mamej, Agnieszka; Połowniak-Wawrzonek, Dorota (Respectus Philologicus, 2019)
The present paper discusses winged words having a source in the lyrics of songs written by W. Młynarski and A. Osiecka. The article also contains examples of such units derived from the texts of other authors, including J. Przybora. The authors chose winged words having their source in the song, because this genre has a strong impact on the Polish language. There are recorded in Polish language, first of all, song titles, repetitive fragments, first of all parts of their choruses. Repeatability of the word relationship in the song favors its recording. In addition to the canonical forms of the analyzed word combinations, for example: W co się bawić; Róbmy swoje; Niech żyje bal! czy Jak dobrze mieć sąsiada, the authors also discuss their various modifications, for example: Lubmy swoje; Jak dobrze znać swojego sąsiada; Jak dobrze mieć tatę. In their considerations, the authors refer to the study of winged words conducted by A. M. Lewicki, W. Chlebda, J. Tarsa and J. Ignatowicz-Skowrońska.
Keywords: winged words; idiom; modifications of winged words; song